Propiedad antibacteriana de un extracto de semilla de Mangifera indica L. sobre Staphylococcus aureus resistente a la meticilina - Noguera Machado, Nirza; Instituto de Investigaciones Biomédicas “Dr. Francisco Javier Triana Alonso” de la Universidad de Carabobo (BIOMED-UC). Maracay-Venezuela/Departamento de Ciencias Básicas de la Escuela de Bioanálisis sede Aragua de la Universidad de Carabobo. Maracay (2021)
The “mango” tree (Mangifera indica L.) have been use in traditional medicine for the treatmentof different ailments. Is a known that diversity extracts of various parts plants have activitymicroorganism pathogenic. In this work were investigated the antimicrobial activity of mangoseeds extract against Staphylococcus aureus methicillin-resistant strains (MRSA) 1025 and 1920. Theseeds extractions prepared by maceration whit ethanol 90%. The phytochemical constituents ofextracts were characterized for total phenol content (TPC) and total flavonoids (TF). Antibacterialactivity of extracts were determined using disk diffusion, agar dilution methods. The resultsshowed that the seeds extracts contents higher to TPC (85.60 ± 2.13 mg EAG/g of extract) and TF(49.32 ± 1.12 mg CE/g of extract). The result revealed that the extracts possess good antibacterialactivity against S. aureus MRSA 1025 and 1920, the inhibition zones ranged from 6.0 mm to 19 mm,at different concentration extracts probed. The results probed that the mango seed extract containedmany compounds such as phenolic that could be affect bacteria S. aureus MRSA, and these bioactivecompounds to be isolated for the production of new antibiotics.